2011
DOI: 10.3389/fpsyg.2011.00099
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed Out of Awareness: EEG Alpha Oscillations Represent a Pulsed-Inhibition of Ongoing Cortical Processing

Abstract: Alpha oscillations are ubiquitous in the brain, but their role in cortical processing remains a matter of debate. Recently, evidence has begun to accumulate in support of a role for alpha oscillations in attention selection and control. Here we first review evidence that 8–12 Hz oscillations in the brain have a general inhibitory role in cognitive processing, with an emphasis on their role in visual processing. Then, we summarize the evidence in support of our recent proposal that alpha represents a pulsed-inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

37
417
4
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 451 publications
(460 citation statements)
references
References 231 publications
(256 reference statements)
37
417
4
2
Order By: Relevance
“…In particular, spiking was more likely to occur at the trough than at the peak of the α-cycle. These findings are consistent with the pulsed-inhibition hypothesis (5,28,29), which states that the α-oscillations are a consequence of bouts of inhibition that prevent firing and thus reduce neuronal processing.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In particular, spiking was more likely to occur at the trough than at the peak of the α-cycle. These findings are consistent with the pulsed-inhibition hypothesis (5,28,29), which states that the α-oscillations are a consequence of bouts of inhibition that prevent firing and thus reduce neuronal processing.…”
Section: Discussionsupporting
confidence: 80%
“…However, given the strong oscillatory nature of the α-activity, it is less clear how it influences processing in a phasic manner. It has been suggested that α-oscillations serve to depress processing every ∼100 ms by a mechanism of pulsed inhibition (5,(28)(29)(30). In support of this notion, it has recently been demonstrated that perception is modulated by the prestimulus phase of the α-rhythm (31, 32).…”
mentioning
confidence: 55%
“…One intriguing proposal is that cortical oscillations instantiate perceptual predictions by coordinating prestimulus neural activity to process the predicted stimulus optimally (1,2). A candidate neural mechanism for such coordination is low-frequency oscillations in the alpha band (8)(9)(10)(11)(12)(13)(14) Hz) of human electroencephalography (EEG) recordings, which are suggested to route information phasically through task-relevant networks (3,4). As evidence, recent work has demonstrated that the prestimulus alpha-band phase predicts visual detection (5,6), the perception of phosphenes (7), the magnitude of the functional MRI (fMRI) response in visual cortex (8), successful perceptual integration across the visual field and subsequent connectivity between visual and parietal cortex (9), as well as variability in working memory performance (10).…”
mentioning
confidence: 99%
“…Trial-to-trial fluctuations in power might account for variations in the detectability of stimuli: A weak stimulus might be sufficient to produce a response from a region in a low-alpha, high-excitability state, but insufficient when that region is in a high-alpha, low-excitability state. Alpha oscillations may thus reflect pulses of cortical inhibition (Mathewson et al, 2011), as a sensory region adjusts to temporal expectations of the delivery of a stimulus by ensuring it is in high-excitability state when a stimulus is expected. Top-down manipulation of alpha power may also be a mechanism for the suppression of irrelevant stimuli (Haegens, Händel, & Jensen, 2011), through the inhibition of cortical regions dealing with, for example, unattended regions of space.…”
Section: Introductionmentioning
confidence: 99%